2020
DOI: 10.1101/2020.09.09.20191643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and temporal trends in social vulnerability and COVID-19 incidence and death rates in the United States

Abstract: Background: Emerging evidence suggests that socially vulnerable communities are at higher risk for coronavirus disease 2019 (COVID-19) outbreaks in the United States. However, no prior studies have examined temporal trends and differential effects of social vulnerability on COVID-19 incidence and death rates. The purpose of this study was to examine temporal trends among counties with high and low social vulnerability and to quantify disparities in these trends over time. We hypothesized that highly vulnerab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…However, the relationship between the overall SVI score and COVID-19 incidence was not statistically significant. In a study by Neelon et al (2020) utilizing COVID-19 cases and deaths within a Bayesian hierarchical negative binomial model between March 1 and August 31, 2020, counties were classified based on SVI composite percentiles (Neelon et al, 2020). Cases and deaths were examined daily for all U.S. counties after adjusting for percentage rural, percentage poor or in fair health, percentage of adult smokers, county average daily PM2.5 and primary care physicians per 100,000.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship between the overall SVI score and COVID-19 incidence was not statistically significant. In a study by Neelon et al (2020) utilizing COVID-19 cases and deaths within a Bayesian hierarchical negative binomial model between March 1 and August 31, 2020, counties were classified based on SVI composite percentiles (Neelon et al, 2020). Cases and deaths were examined daily for all U.S. counties after adjusting for percentage rural, percentage poor or in fair health, percentage of adult smokers, county average daily PM2.5 and primary care physicians per 100,000.…”
Section: Accepted Articlementioning
confidence: 99%
“…The past decade has witnessed an increasing trend in research activity focusing on social and environmental vulnerability as it relates to geophysical and man‐made hazards. More recently, there has been vigorous interest in social vulnerability as it relates to the ongoing COVID‐19 pandemic (Bilal et al., 2020 ; Coelho et al., 2020 ; Dasgupta et al., 2020 ; Gaynor & Wilson, 2020 ; Khazanchi et al., 2020 ; Kim & Bostwick, 2020 ; Lancet, 2020 ; Mishra et al., 2020 ; Mohanty, 2020 ; Neelon et al., 2020 ; Snyder & Parks, 2020 ). Additionally, researchers have attempted to construct COVID‐19‐specific vulnerability indices, examine spatial relationships, or integrate both social and environmental determinants into a complete model, illustrating areas more prone to adverse impacts (Karaye & Horney, 2020 ; Khazanchi et al., 2020 ; Snyder & Parks, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have reported associations between SVI scores and COVID-19 case rates [ 20 22 ]. In addition, an earlier analysis indicated that the socioeconomic status and minority status themes had the strongest correlation with case rates [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…While researchers studied the spatial associations of SDoH with Covid-19 mortality [94] , there is a lack of understanding about the spatiotemporal dynamics of Covid-19 and how it relates to social factors, which is important for state and county-level resource allocations and safe operations of schools and businesses. There are limited research [19] , [20] , [21] , [22] on the spatiotemporal cluster analysis of Covid-19. A recently published study [20] considered Social Vulnerability Indices (SVI) but did not consider differential effects of rurality on SVI.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited research [19] , [20] , [21] , [22] on the spatiotemporal cluster analysis of Covid-19. A recently published study [20] considered Social Vulnerability Indices (SVI) but did not consider differential effects of rurality on SVI. In the U.S., rural/urban residence status creates major healthcare access and health outcomes disparities [23] .…”
Section: Introductionmentioning
confidence: 99%